Population Pharmacokinetics of Polymyxin B in Obese Patients for Resistant Gram-Negative Infections - Wang, Peile; Zhang, Qiwen; Feng, Min; Sun, Tongwen; Yang, Jing; Zhang, Xiaojian (Frontiers in Pharmacology, 2021)
Polymyxin B is an effective but potentially nephrotoxic antibiotic that is commonly used to treat resistant Gram-negative infections. As a weight-based dosing drug, obese patients may be at a high risk of nephrotoxicity. However, the pharmacokinetics and dosing recommendations for this population are currently lacking. This study aimed to describe the polymyxin B population pharmacokinetics and to evaluate pharmacokinetic/pharmacodynamic target attainment for obese patients. This study included 26 patients (body mass index > 30) who received polymyxin B for ≥ 3 days. A two-compartment model adequately described the data using Phoenix NLME software. Monte Carlo simulation was used to assess polymyxin B exposure and the probability of target attainment (PTA). As a result, body weight had no significant effect on polymyxin B pharmacokinetics. According to model-based simulation, adjusted body weight (ABW)-based regimens had a high probability of achieving optimal exposure with minimal toxicity risk by comparing total body weight (TBW)-based regimens and ideal body weight (IBW)-based regimens. PTA results showed that TBW-based regimens, IBW-based regimens, and ABW-based regimens had similar PTA values. Therefore, ABW-based regimens have a high likelihood of achieving an AUCss,24h of 50-100 mg·h/L, and attaining the pharmacokinetic/pharmacodynamic targets with a minimum inhibitory concentration  0.5 mg/L for obese patients.